The Pharmacological Mechanisms Underlying the Protective Effect of Ginsenoside Rg3 against Heart Failure - Yanan Jia; Miao Gong; Zunping Ke (Cardiology Research and Practice)
Background. Heart failure represents the terminal stage of various cardiovascular diseases. This study aims to explore the pharmacological mechanisms underlying the protective effect of Ginsenoside Rg3 against heart failure. Methods. Potential targets of Ginsenoside Rg3 were identified using SwissTargetPrediction and the Comparative Toxicogenomics Database, while heart failure-related genes were retrieved from the Comparative Toxicogenomics Database, Therapeutic Target Database, DisGeNET, and PharmGKB. Overlapping of Ginsenoside Rg3 targets with heart failure-related genes identified drug-disease interaction genes. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were conducted on the drug-disease interaction genes to elucidate their biological functions. A protein-protein interaction network was constructed using the drug-disease interaction genes, and the hub genes were identified by topological analysis. Additionally, we validate the expression of IL-6 and TNF by real-time PCR. Results. The intersection of Ginsenoside Rg3 targets and heart failure-related genes yielded 15 drug-disease interaction genes. Enrichment analysis highlighted the involvement of inflammation-related GO terms and KEGG pathways, such as positive regulation of interleukin-8 and -6 production, regulation of immune effector process, cytokine receptor binding, cytokine activity, adipocytokine signaling pathway, and IL-17 signaling pathway, which are implicated in the cardioprotective effect. Topological analysis revealed four hub genes: STAT3, CASP3, TNF, and IL-6. The application of Ginsenoside Rg3 significantly reversed the elevated levels of IL-6 and TNF in the isoproterenol-treated H9c2 cell line. Conclusions. Our findings suggest that the cardioprotective effect of Ginsenoside Rg3 may be mediated through its anti-inflammation properties. Further research is required to elucidate and validate the detailed cardioprotective mechanisms of Ginsenoside Rg3.